An efficient manufacturing method for I-shaped cross-sectional CFRP beam with arbitrary arrangement of carbon fiber using electro-activated resin molding. Issue 18 (15th September 2020) - Katagiri, Kazuaki; Honda, Shinya; Minami, Sayaka; Kimu, Daiki; Yamaguchi, Shimpei; Ehiro, Takuya; Tomoatsu, Ozaki; Sonomura, Hirosuke; Kawakita, Sonomi; Takemura, Mamoru; Yoshioka, Yayoi; Sasaki, Katsuhiko
Abstract: The I-shaped cross-sectional beam of CFRP (CFRP I-beam) is usually manufactured by the continuous protrusion method. Carbon fibers can only be arranged in the longitudinal direction. The CFRP I-beam with arbitrary arrangement of carbon fiber was manufactured with applying the electro-activated deposition molding method. The carbon fiber fabric was immersed in the deposition solution and energized, epoxy resin precipitated around carbon fiber and impregnated. The resin-impregnated fabric was installed to the mold, and the CFRP I-beam was fabricated. The CFRP I-beam was subjected to three-point bending tests, and the relationship between load-deflection was simulated by finite-element analysis.